Meters‐Long Flexible CoNiO2‐Nanowires@Carbon‐Fibers Based Wire‐Supercapacitors for Wearable Electronics. Issue 8 (4th September 2016) - Ai, Yuanfei; Lou, Zheng; Li, La; Chen, Shuai; Park, Ho Seok; Wang, Zhiming M.; Shen, Guozhen
Abstract : Wire‐supercapacitors have drawn extensive attentions as a promising candidate for future wearable electronic devices. However, the relative lower energy densities and imperfect physical properties (e.g., length, tenacity, flexibility, and stability) seriously hinder their real applications as energy storage devices in wearable electronics. Herein, the fabrication of wire‐supercapacitors is reported with the length of longer than 1 m, based on CoNiO2 ‐nanowires@carbon‐fibers electrodes with a high capacity of 1.68 mF cm −1 and a high energy density of 0.95 mWh cm −3, respectively. The device shows no obvious performance degradation when suffering cycling, bending, pulling, tying, and weaving. After weaving as Chinese knot, watchband, belt, and clothes textile, the wire‐supercapacitors work well as the wearable energy‐storage units to power the personal electronics. Abstract : Wearable 1.2 m long wire‐supercapacitors are fabricated with CoNiO2 ‐nanowires@carbon‐fibers electrodes, which exhibited excellent electrochemical/mechanical performances in terms of high capacitance, excellent stability, and flexibility. The as‐fabricated devices can be portable energy units to power wearable electronics.